Validation of the fisheye camera method for spatial non-uniformity corrections in luminous flux measurements with integrating spheres. (18th June 2019) - Kokka, Alexander; Pulli, Tomi; Ferrero, Alejandro; Dekker, Paul; Thorseth, Anders; Kliment, Petr; Klej, Adam; Gerloff, Thorsten; Ludwig, Klaus; Poikonen, Tuomas; Ikonen, Erkki
Abstract: In this paper, the fisheye camera method is validated for spatial non-uniformity corrections in luminous flux measurements with integrating spheres. The method was tested in eight integrating spheres with six LED lamps, and the determined angular intensity distributions and spatial non-uniformity correction factors were compared with the results of five goniophotometers. The average closeness score, describing the similarity between any two distributions, was 94.6 out of 100 for the distributions obtained using the fisheye camera method when compared with the goniophotometric results. The average closeness score for the five goniophotometers, when each goniophotometer was compared with the other four, was . On average, the relative deviation between the two methods was 0.05% when calculating the spatial corrections. The most significant sources of uncertainty for the fisheye camera method were large, view-obstructing sphere elements residing close to the camera port.